An overview of the treatments for hypertrophic cardiomyopathy - Xu, Wenna; Zhu, Fuyu; Zhang, Yue; Li, Peng; Sheng, Yanhui (Frontiers in Cardiovascular Medicine, 2024)
Hypertrophic cardiomyopathy (HCM) is a very prevalent inherited disease with a wide global distribution and a prevalence rate of approximately 0.2% in the general population. Left ventricular hypertrophy (LVH) caused by sarcomere mutation is the primary reason of HCM. The histopathology feature is that cardiomyocyte hypertrophy, myocyte disorder and myocardial fibrosis lead to diminished diastolic function, left ventricular outflow tract obstruction (LVOTO) and arrhythmia, all of which result in serious cardiac complications. Previously, HCM was considered a malignant disease that was almost untreatable. With the improvement of medical standards and increasing awareness of HCM, it has become a highly treatable disease in contemporary times, with a significant decrease in mortality rates. However, there are still significant unmet requirements in the therapy of HCM. This paper draws on more than 100 references from the past four decades and summarizes current advances in the treatment of HCM. The article will review the pathogenesis and types, recent development in pharmacotherapy, invasive treatments and gene therapies, as well as dilemma and future development of HCM.